UZBEKISTAN’S ROLE IN THE WORLD COMMUNITY AND INTERNATIONAL RELATIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract explores Uzbekistan's evolving role in the global community and its impact on international relations. Situated in Central Asia, Uzbekistan's strategic location has positioned it as a key player in regional dynamics and global affairs. The abstract discusses Uzbekistan's economic reforms aimed at attracting foreign investment and diversifying its economy beyond traditional sectors. Additionally, it highlights Uzbekistan's diplomatic initiatives, emphasizing engagement with neighboring countries and major global powers to promote peace, security, and cooperation. Uzbekistan's contributions to regional security, counterterrorism efforts, and humanitarian assistance underscore its role as a responsible global actor. Looking forward, Uzbekistan's growing influence presents opportunities for deeper international partnerships and collaboration, contributing to regional stability and a more interconnected world.